The Integration of Consonants in Greek Loanwords in Syriac. - Butts, Aaron Michael (Aramaic Studies, 2016)
The present study analyses the integration of consonants in Greek loanwords in Syriac. It is shown that in the vast majority of cases each Greek consonantal phoneme is represented by a single consonant in Syriac. Correspondences that deviate from this are usually the result of one of two causes. First, a Koine form of Greek, instead of Attic, likely served as the source for some of the words that prima facie seem to exhibit irregular correspondences. Second, some of the seemingly irregular correspondences are due to secondary developments in Syriac. This study is based on a corpus of more than eight hundred Greek loanwords and their derivatives found in pre-eighth-century Syriac texts that were not translated from Greek.